Level of patient satisfaction at government Unani & Ayurvedic Medical College Hospital in Dhaka, Bangladesh - Sumaiya Akter Snigdha; Mohammad Morshad Alam; Segufta Dilshad; Shaikh Abdus Salam; Animesh Biswas; Mohammad Delwer Hossain Hawlader (Elsevier, 2020)
Objectives: This study was aimed to assess the level of patient satisfaction at Government Unani & Ayurvedic Medical College Hospital in Dhaka, Bangladesh. Study design: This was a cross-sectional study conducted among 165 patients attended at the out-patient department of Government Unani & Ayurvedic Medical College Hospital, Dhaka, Bangladesh. Patients who were equally or more than 18 years with a history of at least two referral visits were eligible to participate in the study. Methods: Patients satisfaction was measured by the Patient Satisfaction Questionnaire (PSQ-18), composed of 18 items translated in Bangla. Results: Among 165 out-patients, 135 (81.8%) were satisfied and 30 (18.2%) were dissatisfied with medical services. The mean and standard deviation of total patient satisfaction was 69.1 (±16.9). Financial aspects were the major area of patient dissatisfaction 29 (17.6%) towards Unani and Ayurvedic treatment due to lack of free medicine supply and high cost of medicine. Conclusion: The results would shed light on the present conditions of medical services at Government Unani & Ayurvedic Medical College Hospital which could be used to influence the outlook of the policymakers of our country.